CLINICAL FEATURES OF CHILDREN WITH MYCOPLASMA PNEUMONIAE PNEUMONIA COMPLICATED BY PLASTIC BRONCHITIS AND RELATED RISK FACTORS - GAO Lanfang, LI Lei, GUAN Renzheng, WANG Fang, MAO Chenggang, GUO Xingqing, QU Zhenghai (精准医学杂志, 2023)
Objective To investigate the clinical features of children with Mycoplasma pneumoniae pneumonia (MPP) complicated by plastic bronchitis (PB) and related risk factors, and to provide a reference for the early diagnosis and treatment of such disease. Methods A total of 75 children who underwent bronchoscopy and were diagnosed with MPP in our hospital from July 16 to November 6 in 2021 were enrolled, and according to the presence or absence of bronchial plastic casts, they were divided into PB group and non-PB group. Clinical data were compared between the two groups; a logistic regression analysis was used to investigate the risk factors for MPP complicated by PB, and protein mass spectrometry was used to analyze the components of bronchial plastic casts in the children with PB. Results Compared with the non-PB group, the PB group had significantly higher frequency of pyrexia, proportion of children with a duration of fever of ≥10 d, proportion of children with pulmonary consolidation, percentage of neutrophils in bronchoalveolar lavage fluid, erythrocyte sedimentation rate (ESR), and levels of C-reactive protein, lactate dehydrogenase, procalcitonin (PCT), and D-dimer (t=2.290-3.793,χ2=5.548,5.659,Z=-2.085,P<0.05). The multivariate logistic regression analysis showed that PCT level (OR=1.071,95%CI=1.015-1.130,P<0.05) and ESR (OR=1.088,95%CI=1.033-1.146,P<0.05) were risk factors for PB. Protein mass spectrometry showed that the bronchial plastic casts contained rich fibrin. Conclusion Compared with children with MPP alone, children with MPP complicated by PB tend to have a stronger inflammatory response, and the possibility of MPP complicated by PB should be considered in case of ESR >25.20 mm/1 h and PCT >0.19 μg/L. The bronchial plastic casts of children with PB contain a large amount of fibrinogen, which may be associated with the abnormal activation of coagulation-fibrinolytic system due to inflammatory response.